Hiv Stage 4 With Pulmonary Tuberculosis, Collitis Tuberculosis, Oral Candidiasis, Wasting Syndrome, And Sensorineural Deafness: A Case Report - Fadel Fikri Suharto; Edwin Nugraha Fetriawan; Muhamad Satria Yudha Pratama; R. Yudistira Dwi Ananda; Zen Ahmad; Raden Ayu Linda Andriani; Harun Hudari (RSUP Dr Moh Hoesin Palembang, 2021)
Human immunodeficiency virus (HIV) is a retrovirus type virus that infects cells of the human immune system (especially CD4 positive T-cells and major components of the cellular immune system) and interferes with their function. This viral infection results in a continuous decline in the immune system, which will result in immune deficiency. People who are immune deficient/immunodeficiency become more susceptible to various types of infections. A 23 year male, a cafe employee, was admitted to hospital with complaints of weakness since 2 weeks before. He has productive cough for 3 weeks. He had decrease of food appetite, nauseas and vomiting. He had weight loss about 10 kg in the last 4 months. Patient had history of free sex, LGBT, since 2016 and history of hearing loss for 3 months. Laboratory finding showed rhonchi were found at the apex of the right and left lungs, Anti-HIV reactive and Absolute CD-4 count was 53 cell/uL, Gene Xpert MTB was detected, and Acid fast bacilli in stool is positive. Audiometry showed bilateral sensorineural deafness. Patient was diagnosed with HIV stage 4 with pulmonary tuberculosis, tuberculosis collitis, oral candidiasis, wasting syndrome, and sensorineural deafness.